Testicular tumor with clinical picture of febricity of unknown etiology - Andjelic, Sladjana (The Turkish Journal of Pediatrics, 2010)
We present a typical example of a previously healthy boy, whose febricity of unknown etiology lasting for several months was not taken seriously, regardless of the presence of general symptoms of the disease. He was treated as an outpatient with antibiotics and antipyretics under different diagnoses until he was admitted to the Department for Febrile Conditions of Unknown Etiology of the Institute for Infectious Diseases of the Clinical Center of Serbia. At that point, a diagnosis of testicular tumor of extragonadal origin with bilateral metastatic changes of lung parenchyma and retroperitoneal lymph nodes was made, after which the appropriate treatment was administered.